PENGEMBANGAN ATRIBUT PRODUK KERIPIK SINGKONG MENGGUNAKAN METODE VALUE ENGINEERING BERBASIS CUSTOMER ORIENTED - Muhammad Indra Darmawan; Mariatul Kiptiah; Maulida Safitri; Adzani Ghani Ilmannafian (Jurnal Teknologi Industri Pertanian, 2021)
The development of the home industry and the challenges during the pandemic have prompted the need for innovation, especially in the aspect of the marketing mix. The development of this aspect will make MSME products able to compete in the modern retail industry. This effort was implemented in Mr. Baihaqi's cassava chips business, which according to preliminary research needs to develop product aspects, especially on packaging and labels. This study aims to determine recommendations for the development of cassava chips using the value engineering method based on customer oriented. This study aimed to determine recommendations for the development of cassava chips using the value engineering method based on customer oriented. The stages carried out in this study were the information stage by filling out an online questionnaire which is known to be prioritized marketing mix to be developed, namely in terms of packaging and adding labels. The creative stage was carried out by analyzing the morphology of packaging and labels. The analysis stage was carried out by filling out a pairwise comparison questionnaire and analyzed using expert choice 11 software. Development stage with a business feasibility analysis based on Cost of Goods Sold (COGS) and Break Even Point (BEP). The last stage was the recommendation stage for product development presentation. The results showed that the priority of product development was standing pouch plastic packaging using top-bottom labels with a value of 0.160 and COGS of Rp. 4,063.97, BEP of production of Rp. 404,232.27 and BEP units of 57.75 packs. Keywords: marketing mix, cassava chips, value engineering